Risk Of Malignancy Index 4 Performance as a Predictor Advanced Stage Epithelial Ovarian Carcinoma Used for Neoadjuvant Chemotherapy - Tatit Nurseta; Dhian Eka Putri Harnandari; Putu Arik Herliawati; Mukhamad Nooryanto; Puspita Handayani (Medical Laboratory Technology Journal, 2021)
The relatively low survival rate in patients with advanced-stage carcinoma ovaries requires early detection to improve treatment outcomes. The method currently used to determine the administration of neoadjuvant chemotherapy is ascites cytology and laparoscopic. This study aims to find a non-invasive technique in determining preoperative Neoadjuvant Chemotherapy administration, and that method can use as a predictor of advanced epithelial ovarian carcinoma. The benefit of this study is to help clinicians consider administering neoadjuvant chemotherapy with a Risk Of Malignancy Index 4 score. An analytical observational study with a retrospective cross-sectional type study with samples of all patients from January 2016 to January 2020 diagnosed at the dr. Saiful Anwar Hospital in Malang indonesia. The number of initial samples of this study is 106 samples. Between the results of the Risk Of Malignancy Index 4 score and the histopathological results, it finds that the p-value was less than 0.05 (p